2011
DOI: 10.1116/1.3671008
|View full text |Cite
|
Sign up to set email alerts
|

Role of ions, photons, and radicals in inducing plasma damage to ultra low-k dielectrics

Abstract: The damage induced by CO2 and O2 plasmas to an ultra low-k (ULK) dielectric film with a dielectric constant (κ) of 2.2 was investigated. The dielectric constant was observed to increase due to methyl depletion, moisture uptake, and surface densification. A gap structure was used to delineate the role of ions, photons and radicals in inducing the damage, where the experimental variables included an optical mask (MgF2, fused silica, and Si), a gap height, an inductively coupled plasma power source, a bias power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…6 Ming-Shu Kuo et al and Hualiang Shi extensively studied the surface modification of ultralow-k materials by CO 2 plasma and the results are published in their PhD dissertations 7,8 and in several papers. [9][10][11][12][13] They reported that i) CO 2 and O 2 plasma damage to ultralow-k films are comparable ii) there is lower atomic oxygen density in CO 2 discharge than O 2 discharge because of higher activation energy (11.5 eV) required to liberate atomic oxygen from CO 2 than from O 2 molecules (6 eV) -this is why there is supposedly a reduction in damage by CO 2 discharge with respect to O 2 for same operating conditions iii) the ashing rate of CO 2 increases with the addition of Ar at higher pressure (about 100 mTorr) than at lower pressure hence the addition of Ar is beneficial and dependent on pressure. Adding Ar brings about the dilution of the concentration of O 2 atoms that are liberated from CO 2 hence a lower damage to low-k.…”
mentioning
confidence: 99%
“…6 Ming-Shu Kuo et al and Hualiang Shi extensively studied the surface modification of ultralow-k materials by CO 2 plasma and the results are published in their PhD dissertations 7,8 and in several papers. [9][10][11][12][13] They reported that i) CO 2 and O 2 plasma damage to ultralow-k films are comparable ii) there is lower atomic oxygen density in CO 2 discharge than O 2 discharge because of higher activation energy (11.5 eV) required to liberate atomic oxygen from CO 2 than from O 2 molecules (6 eV) -this is why there is supposedly a reduction in damage by CO 2 discharge with respect to O 2 for same operating conditions iii) the ashing rate of CO 2 increases with the addition of Ar at higher pressure (about 100 mTorr) than at lower pressure hence the addition of Ar is beneficial and dependent on pressure. Adding Ar brings about the dilution of the concentration of O 2 atoms that are liberated from CO 2 hence a lower damage to low-k.…”
mentioning
confidence: 99%
“…These results show that the improved mechanical properties are related to the plasma-induced bond rearrangement in the film. As shown in Figure 4 28 It should be noted that these bonding configuration changes are due to a synergy between the effects of energetic charged particles and VUV photons from Ar plasma. 21 Prager et al 29 total number of these bonds over the entire volume of the film is reduced by VUV photon.…”
Section: A Effect Of Energetic Ionsmentioning
confidence: 99%
“…The ion densification layer was observed to be about 30 nm for the plasma-exposed sample. 28 The mechanisms of these energetic-ion-induced "bulk" property changes will be analyzed in detail in the following.…”
Section: A Effect Of Energetic Ionsmentioning
confidence: 99%
“…The bottom electrode sits 3.2 cm from the top electrode. The base case conditions are 150/250/1500 W at 2/14/150 MHz and 100 mTorr gas pressure in CF 4 . The acceleration technique to achieve a quasi-steady state in CW mode is used for 300 cycles of 150 MHz before transitioning into the pulsed mode.…”
Section: Negative Ion Flux In Pulsed Electronegative Plasmasmentioning
confidence: 99%
“…[1][2][3] Plasma etching processes must mitigate plasma-induced damage (PID) which manifests in the form of ion bombardment, photon bombardment, or differential charging damage. [4][5][6] Compared to the continuous wave (CW) plasmas, pulsed plasmas have been shown to demonstrate a lower (time-averaged) electron temperature (T e ) and therefore lower ion energies. 2 The lower electron temperature also decreases the radiation emission in the plasma thereby reducing PID due to photon bombardment.…”
Section: Introductionmentioning
confidence: 99%